A Wounded Soldier Fighting on two Fronts: Civil Society Organizations Initiatives Struggling to Overcome the Pandemic Crisis by Practical Protective Means, Volunteerism, Reporting and Awareness Campaign Discourse - Vllasaj, Kushtrim (International Journal of Engineering and Management Sciences, 2021)
Given the fact that the covid-19 pandemic virus has had a pervasive impact on almost every sphere of life globally, it is noteworthy to highlight the role and position of the civil society sector, and this paper intends to do so by striking at two matters. Initially, outlining the impact on the functioning and activities of Civil Society Organizations (CSOs), to then proceed with their response to the crisis, through new multifarious initiatives/activities. The analysis was developed by using, essentially, unobtrusive data and direct non-participatory observations of Non-Governmental Organizations (NGOs) in Kosovo that have had initiatives against covid-19. Although CSOs were badly affected by the pandemic as such, and the consequences it brought, whether, through measures and/or neglect from the central level, they still found the resources and willingness to launch initiatives to combat the pandemic in the form or different. All over the country, appeared organizations which among their activities found a place for awareness campaigns, material and financial assistance to citizens in need, production of masks, face shields, and other protective equipment for citizens or health institutions, and providing voluntary assistance as health staff. To link practice with theory, there are presented cases of NGOs that well reflect scholarship ideas such as the need to have a classification of CSOs based on activities, the importance of their IT repertoires, coproduction, and especially the response to the crisis. The importance of this study grounds on the benefit it brings to understanding the role and contribution of CSOs in exceptional times of crisis, especially for a society that underestimates and neglects this sector.